Risk compensation and bicycle helmets: A false conclusion and uncritical citations. (October 2018) - Radun, Igor; Radun, Jenni; Esmaeilikia, Mahsa; Lajunen, Timo
Highlights: Few empirical studies exist on the topic of risk compensation and bicycle helmets. Such a lack of studies means that the impact of a single study can be significant. We show how one of the rare experimental studies arrives at a false conclusion. And is cited as evidence that helmeted (male) cyclists take more risks. We discuss potential consequences of false conclusions and uncritical citations. Abstract: Some researchers and many anti-helmet advocates often state that when cyclists wear a helmet they feel safer and take more risks. This hypothesis – risk compensation – if true, would reduce, annul or even reverse the assumed benefits of helmets in reducing head injuries. Consequently, this hypothesis is often used to oppose mandatory helmet laws. In this article, we illustrate how one of the few studies that attempted to experimentally test the hypothesis in relation to bicycle helmets arrives at a false conclusion. As a result it is often cited as evidence of risk compensation. Given the lack of experimental studies in this research area, the impact of a single study in shaping the opinions of the general public and of policy makers can be significant.